Investigation of aflatoxin levels in chips by HPLC using post-column UV derivatization system - Çatak, Jale; Yaman, Mustafa; Uğur, Halime (Progress in Nutrition, 2020)
This study was designed to investigate the aflatoxin B1 (AFB1), B2 (AFB2), G1(AFG1), G2(AFG2) and total aflatoxin levels in 27 samples of several packaged chips randomly obtained from various markets in Istanbul using immunoaffinity chromatography and post-column UV derivatization system by HPLC. Seventeen of the samples contained some aflatoxins at detectable levels, whereas 10 did not. The levels of aflatoxin ranged between 1 and 39 μg/kg. AFB1 and AFB2 were detected in 63% and 41% in analyzing chip samples respectively. The levels of AFB1 varied from 1 to 24 μg/kg in chip samples and the levels of AFB2 varied from 1 to 16 μg/kg in chip samples. Low levels of AFG2 ranging from 0 to 3 μg/kg were found in chips. Groundnut chips showed high aflatoxin concentrations and recorded relatively higher AFB1, AFB2, AFG2 and Total aflatoxin levels ranging from 1 to 39 μg/kg, indicating that groundnut is potentially causing serious health risks to consumers of these products than other chips. The aim of this study is to determine the presence and amount of aflatoxin B1, B2, G1, G2 in various chips samples consumed in Istanbul.